PENGARUH LEVERAGE DAN GROWTH OPPORTUNITIES TERHADAP KEBIJAKAN DEVIDEN PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2009-2011 - WIBOWOPUTRA, ALOYSIUS STEVEN (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
This study aims to see the effect of leverage as measured using the debt to total asset of the company’s and the effect of growth opportunity of company’s as measured by price earing ratio to company’s devidend policy. This study uses secondary data by the number of samples used by 35 manufacturing companies listed on the Indonesia Stock Exchange during the three-year period 2009-2011 and has met certain criteria. The result showed that the debt to total asset negatively affect the devidend policy. This can be explained that the higher debt, it will be able to increasing the expenses of earning after tax that should be able to be paid for cash devidend. While the results of subsequent research found that the price earning ratio aslo has a negative effect on corporate devidend policy. This can be explained that the bigger chance of company’s growth will make their manager to buy an investment rather than pay the cash devidend.